Characteristics of Human Antibody to Diphtheria Toxin - Bazaral, M. (1973)
Human antibody to diphtheria toxin was analyzed with an ammonium sulfate radioimmunoassay. In 15 immune sera with titers of between 0.03 and 25 units/ml, the avidity was similar to that of U.S. standard antitoxin. The proportion of the post-immunization anti-diphtheria antibody specific for fragment A was variable, but in the 10 sera tested constituted a substantial fraction of the antibody. Approximately 2% of healthy adult males tested failed to make an antidiphtheria toxin response after two booster doses of 1.5 Lf adsorbed diphtheriatetanus toxoid, although these nonresponders made precipitating antibody to tetanus toxoid and had normal immunoglobulin levels.